"SOCIAL-PSYCHOLOGICAL FEATURES OF FORMING POSITIVE ATTITUDES IN STUDENTS OF JUNIOR SCHOOL AGE" - Usmonov Sherzod Axmadjonovich; Mamaziyayeva Charosxon Mirzamirovna (Journals Park Publishing, 2022)
Preparing the youth of our republic, which is on its way to independent development, for a new social environment, educating them in the spirit of the times is one of the urgent and priority tasks. The development of the reforms implemented in our republic depends on the spiritual image and personal integrity of young people in many ways.